Unlocking the Therapeutic Essence of Hingwadi Agada: An Ayurvedic Heritage In Healing Practices (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra is an essential part of Ashtanga Ayurveda, dealing with the clinical aspects of poisoning, including its identification and therapeutic interventions. Vrischika visha is one of the critical clinical conditions requiring emergency care. Various antidotal formulations in Ayurveda known as Agada Yoga’s (anti-toxic formulations) are useful in Vrischika Visha Chikitsa. Hingwadi Agada is one of the Agada Yoga’s mentioned by Acharya Vagbhatta in Ashtanga Hridaya. Aim and objectives: Based on the function of Hingwadi Agada ingredients are described in various classical texts, this review and debate will focus on Vrischika Visha Damsha. Materials and Method: Several classical texts were referred, namely Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Ashtanga Sangraha, various Nigantus and textbooks like the Dravyaguna Vigyana and Peer Review articles. Observations and Results: According to Acharya Vagbhatta, Hingwadi Agada includes two main ingredients along with a single processing medium all of which possess properties such as Deepana (appetite-stimulating), Pachana (digestive enhancing), Shulahara (analgesic). Sothahara (anti-inflammatory), Sonithsthapana (blood stabilizing), Vatanuloma (regulating the Vata Dosha etc. Conclusion: According to Acharya Vagbhatta's Vrischika Damsha Chikitsa, Hingwadi Agada holds potential as an effective antidote and deserves to be explored through clinical and experimental trials for treating Vrischika Visha.